2012
DOI: 10.1021/jo202366c
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (±)-Rocaglamide via Oxidation-Initiated Nazarov Cyclization

Abstract: This article describes the evolution of a Nazarov cyclization-based synthetic strategy targeting the anticancer, antiinflammatory, and insecticidal natural product (±)–rocaglamide. Initial pursuit of a polarized heteroaromatic Nazarov cyclization to construct the congested cyclopentane core revealed an unanticipated electronic bias in the pentadienyl cation. This reactivity was harnessed in a successful second-generation approach using an oxidation-initiated Nazarov cyclization of a heteroaryl alkoxyallene. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 115 publications
2
31
0
Order By: Relevance
“…In 2012, Frontier and coworkers 49 disclosed the total synthesis of (±)-rocaglamide ( 1 ) while the Magnus group 50 reported a formal synthesis of (±)-methyl rocaglate ( 42 ). Both approaches utilized a Nazarov cyclization as the key step for the preparation of the tricyclic rocaglamide core.…”
Section: Update On Synthetic Methods For Cyclopenta[b]benzofuransmentioning
confidence: 99%
“…In 2012, Frontier and coworkers 49 disclosed the total synthesis of (±)-rocaglamide ( 1 ) while the Magnus group 50 reported a formal synthesis of (±)-methyl rocaglate ( 42 ). Both approaches utilized a Nazarov cyclization as the key step for the preparation of the tricyclic rocaglamide core.…”
Section: Update On Synthetic Methods For Cyclopenta[b]benzofuransmentioning
confidence: 99%
“…Flavagline synthesis remains a challenge as the compounds have two contiguous quaternary chiral centers and cis aryl groups on adjacent carbons of a strained cyclopentane ring. Since most of these efforts have already been reviewed, we will discuss only the most recent developments in this field [3,4,12].…”
Section: Synthesesmentioning
confidence: 99%
“…1 H NMR and 13 C NMR spectroscopy were performed at ambient temperature. 2-Bromocyclohex-1-enecarbaldehyde, 12 phenylboronic acid– d 5 , 13 and 4,6-dimethoxy-2-(4-methoxyphenyl)benzofuran-3-carbaldehyde ( 5a ) 1b were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported our synthetic efforts toward the synthesis of the cytostatic natural product (±)-rocaglamide 1 , in which the key step was an oxidation-initiated Nazarov cyclization 2 of a benzofuryl allene intermediate. During these studies, we found that treatment of propargylic ether 1a with a substoichiometric amount of Triton B® in DMSO was the most effective way to isomerize 1a to terminal allene 2 (Scheme 1).…”
mentioning
confidence: 99%